Stable and efficient generation of functional iPSC-derived neural progenitor cell rosettes through regulation of collective cell-cell behavior - Kim, Mee-Hae; Thanuthanakhun, Naruchit; Kino-oka, Masahiro (Frontiers in Bioengineering and Biotechnology, 2024)
Although the potential of stem cells to differentiate into several cell types has shown promise in regenerative medicine, low differentiation efficiency and poor reproducibility significantly limit their practical application. We developed an effective and robust differentiation strategy for the efficient and robust generation of neural progenitor cell rosettes from induced pluripotent stem cells (iPSCs) incorporating botulinum hemagglutinin (HA). Treatment with HA suppressed the spontaneous differentiation of iPSCs cultured under undirected differentiation conditions, resulting in the preservation of their pluripotency. Moreover, treatment with HA during neural progenitor differentiation combined with dual SMAD inhibition generated a highly homogeneous population of PAX6-and SOX1-expressing neural progenitor cells with 8.4-fold higher yields of neural progenitor cells than untreated control cultures. These neural progenitor cells formed radially organized rosettes surrounding the central lumen. This differentiation method enhanced the generation of functional iPSC-derived neural progenitor cell rosettes throughout the culture vessel, suggesting that the regulation of collective cell-cell behavior using HA plays a morphogenetically important role in rosette formation and maturation. These findings show the significance of HA in the suppression of spontaneous differentiation through spatial homogeneity. The study proposes a novel methodology for the efficient derivation of functional iPSC-derived neural progenitor cell rosettes.